URBAN TRANSFORMATIONS IN THE AFTERMATH OF LISBON'S EXPO'98 The Polis Programme - Pinto, Paulo Tormenta; Brandão, A.; Cayolla, I.; Costa, J. (XII Seminario Internacional de Investigación en Urbanismo, Lisboa-São Paulo, 2020)
The paper aims to present preliminary results of an ongoing research about the impacts of the 1998 Lisbon World Exposition on the Portuguese architecture and urban planning promoted on the last decades. Specifically, the study addresses the Polis Programme of environmental and urban requalification of medium cities, a national level urban regeneration initiative developed in the aftermath of the mega-event in Lisbon. The research analyses the programme set-up and implementation in order to draw conclusions on the programme achievements and its connections to the Lisbon exhibition. Results point a newfound interest in public space, with new typologies and uses, improvement efforts of the cities’ image and technical know-how dissemination. Based on these findings, the paper furthers a discussion on the contemporary repercussions of these events and programs.